2020
DOI: 10.1080/09064702.2020.1727560
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the genetic diversity conserved in the Norwegian live poultry genebank

Abstract: The aim of this study was to evaluate genetic diversity within and between lines at the Norwegian live poultry gene bank as well as assessing the conservation value in an international context. Eight lines including the national breed, Jaerhøns, were genotyped with the 600K Affymetrix® Axiom® Chicken Genotyping Array. The white egg layers were generally more inbred than the brown layers. Comparative analyses were carried out with 72 international populations of different origins. The lines that were last bred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Similar ranges in F st have been reported for breeds considered to be quite distinct ( Faria et al, 2019 ; Zhang et al, 2018 ). However, Brekke et al (2020) reported an F st of 0.426 for Plymouth Rock and Rhode Island Red but they also reported these breeds to have inbreeding levels that exceeded 50% (vs. <6% in this study) which could explain the reported differences. The levels of F st for US developed composite breeds, Rhode Island Red, Plymouth Rock, New Hampshire, Jersey Giant, and Buckeye, suggest a level of distinctness and structure has been obtained since breed formation.…”
Section: Discussioncontrasting
confidence: 46%
“…Similar ranges in F st have been reported for breeds considered to be quite distinct ( Faria et al, 2019 ; Zhang et al, 2018 ). However, Brekke et al (2020) reported an F st of 0.426 for Plymouth Rock and Rhode Island Red but they also reported these breeds to have inbreeding levels that exceeded 50% (vs. <6% in this study) which could explain the reported differences. The levels of F st for US developed composite breeds, Rhode Island Red, Plymouth Rock, New Hampshire, Jersey Giant, and Buckeye, suggest a level of distinctness and structure has been obtained since breed formation.…”
Section: Discussioncontrasting
confidence: 46%
“…Though distinct from other commercial populations, the newly developed Norwegian commercial lines were closely related to them. These Norwegian Genebank lines were therefore believed to be of conservation value at national and international levels [Brekke et al, 2020].…”
Section: Development and Application Of Snp Arrays For The Assessment...mentioning
confidence: 99%
“… 1 Information on origin is based on literature review; 2 Personal communication from Mette Nafstad Bjerkestrand, the Norwegian live poultry gene preservation bank, Hvam Agricultural College; 3 Data from Lyimo et al 2014 [ 43 ]; 4 Data from Brekke et al 2017 [ 44 ]. …”
Section: Figurementioning
confidence: 99%